Lecturer Support in the Implementation of a New Curriculum During the COVID-19 Pandemic - Sanderson, Abel; Mafugu, Tafirenyika (Springer, 2022)
The objective of the study was to assess the support provided to lecturers in the implementation of a new curriculum during the COVID-19 pandemic to suggest early intervention strategies that address resources and knowledge deficiency gaps that have a negative impact on curriculum implementation. A survey design was used in the study. A representative sample of 30 lecturers was randomly selected from 5 Faculty of Natural Resources Management and Agriculture departments to complete the questionnaire between June and July 2020. The majority of the lecturers agreed that they were involved in the curriculum development. There was affirmation on the issue of professional development, leadership’s support for lecturers’ curriculum implementation and adequate time for curriculum implementation. Similarly, there was collaboration between university leadership and lecturers to plan curriculum implementation. On the contrary, funds for research necessary for curriculum implementation, instructional materials and supplies and technological resources were not adequately supplied. Hence, the paper becomes critical as it highlights the unavailability of technological resources which play a crucial role in online teaching and learning during the COVID-19 pandemic.